Missouri Municipal Ethics Survey: Do Ethics Measures Work at the Municipal Level?. (2nd July 2016) - Siewert, Wally; Udani, Adriano
Abstract : This article addresses the marked lack of scholarly work correlating common measures meant to improve ethical performance in local government (ethics codes and training) with actual levels of unethical behavior. Analyzing data from a survey specifically optimized to encourage honest reporting on ethical infractions, and administered to local government officials and employees in Missouri, this study is the first of its kind to adopt Lasthuizen's typology of governmental ethical infractions. Results suggest that ethics training regimens (but not ethics codes by themselves) are correlated with measurable drops in reported levels of several of the most commonly observed ethical infraction types, though the relationship is more complex than previously reported. A surprising finding is that larger municipalities were subject to higher infraction rates, but were not more likely to implement ethics measures, indicating that these are the lowest-hanging fruit regarding ethics reforms. Further implications are discussed regarding the content and limited impact of ethics training, leading to recommendations for both practitioners and researchers regarding the full range of ethics measures.